2000
DOI: 10.1021/ol991391t
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular [4 + 2] Cycloaddition Reactions of Diarylacetylenes:  Synthesis of Benzo[b]fluorene Derivatives via Cyclic Allenes

Abstract: 2-Propynyldiarylacetylenes undergo thermal intramolecular [4 + 2] cycloaddition to give benzo[b]fluorene derivatives in good yields. The hybridization of the tether connecting the reacting alkynes has a pronounced effect on the course of the reaction. Theoretical calculations and isotopic labeling studies support a mechanism which involves the generation of a cyclic allene intermediate that evolves to the final benzo[b]fluorene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 27 publications
0
47
0
1
Order By: Relevance
“…Aryl amines (78) forms Pd II chelate complex that leads to a five-membered complex (79). Oxidative addition took place to form Pd IV complex (80) and reductive addition furnished ortho arylated product 81.…”
Section: Intermolecular Synthesis Of Fluorenonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aryl amines (78) forms Pd II chelate complex that leads to a five-membered complex (79). Oxidative addition took place to form Pd IV complex (80) and reductive addition furnished ortho arylated product 81.…”
Section: Intermolecular Synthesis Of Fluorenonesmentioning
confidence: 99%
“…Benzodiynone (190) underwent thermal cycloaddition in toluene at 150°C for 11 h lead to 191 and 192 in 72 % and 24 % of fluorenone (Scheme 66). [78] Recently, Hoye et al reported a new protocol for the synthesis of substituted fluorenones via benzyne cascade reaction. Thermal isomerization of tri-yne benzyne (193) via hexadehydro-Diels-Alder (HDDA) reaction led to substituted fluorenones in moderate to good yields (Scheme 67).…”
Section: Intramolecular Synthesis Of Fluorenonesmentioning
confidence: 99%
“…Another approach by Mal et al was based on ring contraction via the benzil-benzilic acid rearrangement of benzo[a]anthracene-5,6-diones [16]. Other noteworthy approaches are those utilizing [4+2] cycloadditions [17,18], other cycloadditions [17,19,20], and oxidative free radical cyclizations [21]. Birman and co-workers achieved the rapid ring construction of benzo[b]fluorenones via reaction of 1-indanone dianions with phthalate diesters.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Saá and co-workers have extensively studied similar arylalkyne-alkyne cycloadditions. [28,29] In this paper, we report full details of our work, directed towards the synthesis of kinamycins based on the intramolecular reaction of arylalkynes with allenes or alkynes.…”
Section: Introductionmentioning
confidence: 99%